Bleaching-Associated Changes in the Microbiome of Large Benthic Foraminifera of the Great Barrier Reef, Australia - Prazeres, Martina (Frontiers in Microbiology, 2018)
Ocean warming is known to cause detrimental effects in coral reef fauna that rely on photo-symbiosis for survival. Microbial associations can facilitate the success of species across a range of environmental conditions, and play a role in the capacity of organisms to respond to climate change. In 2016, the Great Barrier Reef experienced its third mass bleaching event, with sea surface temperature rising to 1.3°C above long-term monthly summer averages. Here, I investigate the effects of ocean warming on the chlorophyll a (chl a) content and microbiome of the large benthic Foraminifera Amphistegina radiata. Samples were collected in January and April 2016, before and after the mass bleaching event. In total, 71 specimens were collected from two different depths (6- and 18-m) to investigate depth-dependant responses associated with changes in chl a and microbiome. Pigment analysis showed a significant reduction in chl a between time points in specimens collected at both depths. Reduction in pigmentation was accompanied by changes in the microbiome, and a significant interaction of depth and time was observed. Genus-level bacterial community associated with A. radiata was significantly different across depth and time. However, ocean warming affected populations at both depths to a similar extent, and resulted in change from a Betaproteobacteria-dominated assemblage in January to a more diverse bacterial community by April. Analysis of presence/absence and relative abundance of bacterial taxa revealed significant differences between time points at both depths analyzed. OTUs classified as Firmicutes, which were either absent, or present in very low relative abundances (<0.1%) across all sample groups in January, were identified in abundances as high as ∼20% in specimens collected from 18-m depth in April. Class-level shifts were observed in shallow-dwelling specimens, from high abundances of Betaproteobacteria to a high abundance and diversity of Actinobacteria. These results demonstrate the sensitivity of LBF to the effects of ocean warming, for which depth did not provide protection, and highlights the capacity of LBF to re-assemble bacterial communities after a disturbance. This study provides the first molecular-based demonstration of changes in foraminifera-associated bacterial assemblages during a bleaching event on a natural reef system.